Kebisingan dan Stres Kerja pada Karyawan SPBU Kecamatan Medan Area - Dewi Yunita Sembiring; Tri Niswati Utami (FORIKES, 2022)
Public Fuel Filling Station (SPBU) is a location that has a high potential for noise exposure because it is located on a highway, where noise can affect workers. The purpose of the study was to determine the relationship between noise in the workplace and work stress on gas station employees, Medan Area District. The design of this study was cross-sectional. The research subjects were selected using the total population sampling technique. The measuring instrument used to determine the noise level was a sound level meter and a questionnaire distributed to see the level of hearing loss due to noise. Data were analyzed using Chi square test. The results of the study showed the value of p = 0.02. Furthermore, it is concluded that there is a relationship between noise in the workplace and work stress for gas station employees.Keywords: noise; work stress; employeeABSTRAK Stasiun Pengisian Bahan Bakar Umum (SPBU) adalah sebuah lokasi yang mempunyai potensi tinggi terpapar kebisingan karena letaknya berada di jalan raya, di mana kebisingan dapat mempengaruhi pekerja. Tujuan dari penelitian adalah untuk mengetahui hubungan atara kebisingan di tempat kerja dengan stress kerja pada karyawan SPBU Kecamatan Medan Area. Desain penelitian iniadalah cross-sectional. Subyek penelitian dipilih dengan teknik total population sampling. Alat pengukur yang dipakai untuk mengetahui tingkat kebisingan yaitu sound level meter dan kuesioner yang dibagikan untuk melihat tingkat gangguan pendengaran akibat kebisingan. Data dianalisis menggunakan uji Chi square. Hasil dari penelitian menunjukkan nilai p = 0,02. Selanjutnya disimpulkan bahwa adan hubungan kebisingan di tempat kerja dengan stress kerja pada karyawan SPBU.Kata kunci: kebisingan; stres kerja; karyawan